Slovenia: Rights and Discrimination - Elena Pečarič (Social Work & Society, 2006)
Recent events regarding the publication of the health status report of two Slovenian politicians (a member of European Parliament and President of the Republic of Slovenia) drove me to reflect on, describe and compare the two events with common practice, which pertains to disabled persons. The public is disgusted by the fact that health status of so important and influential individuals was made public by none other than a (retired) doctor. However, no one even flinches, let alone is disgusted by the fact that such things happen to people with the status of a disabled person. No one even thinks such doing is wrong, although personal information is disclosed to the public on a common basis. It is expected from disabled persons to get used to such maltreatment and stop complaining. Of course these people are not widely known to the public and their health and social status is useless to anyone but the people who make money by abusing the information they have about them. Therefore, no one seems to care that their files, documents and expert opinions regarding their health and social welfare are being passed among various institutions, disabled persons societies and experts. Consent of the individual is rarely requested or required as the affected persons are seldom notified about such matters. Disabled persons are usually unaware about the content of their files and are thus unable to challenge or express doubts about the correctness of expert reports and examination results. How could a layman even think of having doubts about expert's opinions? Mistakes, errors and abuses are often made, however an individual only rarely gets a chance to point them out. Expert opinions, judgements and decisions carry much more weight than an opinion of an individual who is, on top of that, disabled. Experts have the power of authority and the authority of power and are backed by institutions that are part of the system. The only means left is civil action (provided, of course, that the individual has the proper financial backing for such a feat), however, in our experience taking matters to the court borders to masochism. To add insult to injury, most lawyers won't take such cases because they don't believe they have any chance to win.